Early Brain Injury: A Common Mechanism in Subarachnoid Hemorrhage and Global Cerebral Ischemia - Mohammed Sabri; Elliot Lass; R. Loch Macdonald (Stroke Research and Treatment)
Early brain injury (EBI) has become an area of extreme interest in the recent years and seems to be a common denominator in the pathophysiology of global transient ischemia and subarachnoid hemorrhage (SAH). In this paper, we highlight the importance of cerebral hypoperfusion and other mechanisms that occur in tandem in both pathologies and underline their possible roles in triggering brain injury after hemorrhagic or ischemic strokes.